Biochemical and Molecular Characterization of Bangladeshi Wheat Varieties for Bread-Making Quality (Plant Tissue Culture and Biotechnology, 2018)
Twenty-six wheat genotypes including 18 Bangladeshi varieties and 8 varieties/lines collected from different countries were evaluated for their breadmaking quality. Total grain protein content was measured using Kjeldahl method. Presence of the high molecular weight glutenin subunits (HMW-GS) and their corresponding genes were characterized through SDS-PAGE and PCR based methods. Total protein content of 53.85% of the genotypes ranged between 12 and 14% which is considered as a suitable range of protein for making bread. At the Glu-A1 locus, Ax2* alleles were found with a frequency of 84.62%. At the Glu-B1 locus, 4 different alleles; Bx7, Bx7+By8, Bx7+By9 and Bx17+By18 were detected. At the Glu-D1 locus, PCR test result showed that 61.11% Bangladeshi wheat varieties contain Dx5+Dy10, regarded as the best allele for making bread. Four genotypes, Kalyansona, Sonora-64, Pavon-76 and BARI Gom 28, were found to have the highest quality score of 10. Among those, Kalyansona and BARI Gom 28 had the best HMW-GS combination of Ax2*, Bx17+By18, Dx5+Dy10 and Ax2*, Bx7+By8, Dx5+Dy10, respectively. This study will be important for specifying wheat genotypes for the food industry and further breeding for bread-making quality.Plant Tissue Cult. & Biotech. 28(1): 57-68, 2018 (June)